Mortality in people with mental disorders in the Czech Republic: a nationwide, register-based cohort study - Krupchanka, Dzmitry; Mladá, Karolína; Winkler, Petr; Khazaal, Yasser; Albanese, Emiliano (The Lancet. Public health, 2018)
BACKGROUND: The region of central and eastern Europe is estimated to have high rates of premature mortality due to mental disorders. However, epidemiological evidence is scarce and insufficient to inform policy actions and health system development. We aimed to assess mortality associated with mental disorders in the Czech Republic. METHODS: We did a nationwide, register-based, retrospective cohort study using routinely collected health data from two nationwide registries in the Czech Republic: the register of inpatient discharges (from Jan 1, 1994, to Dec 31, 2013) and the causes of death registry (from Jan 1, 1994, to Dec 31, 2014). We first identified all individuals discharged from mental health institutions with WHO International Classification of Diseases tenth edition (ICD-10) diagnoses of mental and behavioural disorders (from 1994 to 2013). We then did a deterministic individual-level linkage of these data with all-cause mortality data for the whole period (1994-2014). Standardised mortality ratios (SMRs) and 95% CIs were calculated for the year 2014, comparing deaths in people with mental and behavioural disorders discharged from psychiatric hospitals with deaths in the general population. FINDINGS: The final study population comprised 283 618 individuals. 3819 of these individuals died in 2014, corresponding to a mortality risk more than two times higher than that of the general population (SMR estimate 2·2; 95% CI 2·2-2·3). Differences in SMR estimates across diagnostic groups were substantial, with the highest SMR for substance use disorders (3·5; 95% CI 3·4-3·7) followed by schizophrenia, schizotypal, and delusional disorders (2·3; 2·1-2·5), personality disorders (2·3; 2·0-2·6), neurotic, stress-related, and somatoform disorders (1·8; 1·6-1·9), and mood (affective) disorders (1·6; 1·5-1·7). INTERPRETATION: Mortality among people with mental disorders in the Czech Republic is markedly higher than in the general population. Our findings should stimulate and inform policy in the central and eastern Europe region, as well as ongoing national mental health-care reforms in the Czech Republic. FUNDING: Czech Ministry of Education, Youth and Sports.
Keywords: Mental Disorders; duševní poruchy; Cohort Studies; Female; Registries; Adult; dospělí; Humans; ženské pohlaví; Česká republika; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; registrace; Czech Republic; kohortové studie